Pengaruh Media Pembelajaran Natural Picture Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPA - Ruril Rudianto; Supiana Dian Nurtjahyani (BIO-PEDAGOGI, 2018)
Science is a science that learns about life in the world from all aspects. To be able to study these subjects requires a deeper understanding of the material. Application of learning innovations needs to be done to achieve the objectives of science subjects especially by teachers so as to provide hands-on experience for students to acquire innovative learning. Based on the observations at SMP Negeri 1 Bancar known that the results obtained by students less satisfactory. The process of teaching and learning is done by lecture method, when the learning process takes place many students are sleepy and chatting. To improve the learning outcomes in science subjects especially biology required the existence of learning innovation, namely by using Natural Picture learning media. The purpose of this study is to determine whether there is an influence of Natural Picture learning media on student learning outcomes in science biology subjects in SMP Negeri 1 bancar. The type of research used is Quasi Eksperimen. This research was conducted at SMP Negeri 1 Bancar with research sample that is student of class VII A which amounted to 32 students as experiment class and student of class VII E which amounted to 32 students as control class. The research design used was Pre-Test research design - Post-Test Control Group Design. Based on the results of data analysis of learning results, the average value in the experimental class given treatment using Natural Picture learning media is higher than the control class using the lecture method. The experiment class is 87.12 and the control class is 74.37. In the hypothesis test the Sig value. (2-tailed) of 0.000, when compared with α 0.05 then Sig <α then H0 is rejected and H1 accepted. Thus, it can be concluded that there is a difference in mean values of experimental class learning outcomes and control classes. That is, there is the effect of learning media Natural Picture on student learning outcomes.